Application of behavioural theories, models, and frameworks in pharmacy practice research based on published evidence: a scoping review - Zachariah Nazar (8600154) (2024)
Background Pharmacy practice research often focuses on the design, implementation and evaluation of pharmacy services and interventions. The use of behavioural theory in intervention research allows understanding of interventions’ mechanisms of action and are more likely to result in effective and sustained interventions. Aim To collate, summarise and categorise the reported behavioural frameworks, models and theories used in pharmacy practice research. Method PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science and EBSCO (CINAHL PLUS, British Education index, ERIC) were systematically searched to capture all pharmacy practice articles that had reported the use of behavioural frameworks, theories, or models since inception of the database. Results were filtered to include articles published in English in pharmacy practice journals. Full-text screening and data extraction were independently performed by two reviewers. A narrative synthesis of the data was adopted. Studies were reviewed for alignment to the UK Medical Research Council (MRC) framework to identify in which phase(s) of the research that the theory/model/framework had been employed. Results Fifty articles met the inclusion criteria; a trend indicating an increasing frequency of behavioural theory/frameworks/models within pharmacy practice research was identified; the most frequently reported were Theory of Planned Behaviour and Theoretical Domains Framework. Few studies provided explicit and comprehensive justification for adopting a specific theory/model/framework and description of how it underpinned the research was lacking. The majority were investigations exploring determinants of behaviours, or facilitators and barriers to implementing or delivering a wide range of pharmacy services and initiatives within a variety of clinical settings (aligned to Phase 1 UK MRC framework). Conclusion This review serves as a useful resource for future researchers to inform their investigations. Greater emphasis to adopt a systematic approach in the reporting of the use of behavioural theories/models/frameworks will benefit pharmacy practice research and will support researchers in utilizing behavioural theories/models/framework in aspects of pharmacy practice research beyond intervention development. Other Information Published in: International Journal of Clinical Pharmacy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11096-023-01674-x